INTERNATIONAL TRADE: HOW DATA PROTECTION REGULATIONS IMPACT CROSS-BORDER BUSINESS - Kamarova , Zarina Behzod kizi (Educational Research in Universal Sciences, 2024)
In today's interconnected world, the flow of data across borders fuels international trade and drives economic growth. However, this digital highway is increasingly congested by a patchwork of data privacy regulations enacted by individual nations. This article navigates this complex landscape, analyzing how diverse regulatory frameworks impact cross-border business operations. Examining key jurisdictions like the EU, US, and China, the article identifies the challenges companies face, including compliance burdens, data transfer restrictions, and potential discrimination based on national data protection standards. It also explores efforts towards harmonization and convergence, such as APEC's Cross-Border Privacy Rules, and discusses the potential future scenarios for this evolving domain. Ultimately, this article provides insights for policymakers and businesses to adapt and thrive in a data-driven world where balancing individual privacy and global trade is paramount.